2019
DOI: 10.3892/mmr.2019.10404
|View full text |Cite
|
Sign up to set email alerts
|

Application of amplitude of low‑frequency fluctuation to altered spontaneous neuronal activity in classical trigeminal neuralgia patients: A resting‑state functional MRI study

Abstract: Recent studies have reported structural and functional abnormalities in multiple brain regions of classical trigeminal neuralgia (CTN) patients. Differences in spontaneous neuronal activity between CTN patients and healthy subjects, however, remain unknown. The aim of the present study was to investigate alterations in brain activity by application of amplitude of low frequency fluctuation (ALFF), thus analyzing the correlation between durations of spontaneous pain intensity and ALFF values in CTN patients. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 47 publications
(41 reference statements)
0
28
0
Order By: Relevance
“…65,67 In addition to structural changes, fMRI studies demonstrated different patterns of brain activation in patients with TN when compared to healthy controls. 66,68,69,[74][75][76] A different pattern of activation was also observed in TN patients who report pain after stimulation of trigger zones versus patients who do not. 68 Patients with pain evoked by light tactile stimulation showed a bilateral activation of the primary and secondary somatosensory cortices, the ACC, and the prefrontal cortex, contralateral activation of insula and thalamus, ipsilateral activation of the medial cingulate cortex and spinal trigeminal nucleus, and activation of the medial brainstem, including the periaqueductal gray.…”
Section: Pathophysiology Of Classical Tnmentioning
confidence: 93%
“…65,67 In addition to structural changes, fMRI studies demonstrated different patterns of brain activation in patients with TN when compared to healthy controls. 66,68,69,[74][75][76] A different pattern of activation was also observed in TN patients who report pain after stimulation of trigger zones versus patients who do not. 68 Patients with pain evoked by light tactile stimulation showed a bilateral activation of the primary and secondary somatosensory cortices, the ACC, and the prefrontal cortex, contralateral activation of insula and thalamus, ipsilateral activation of the medial cingulate cortex and spinal trigeminal nucleus, and activation of the medial brainstem, including the periaqueductal gray.…”
Section: Pathophysiology Of Classical Tnmentioning
confidence: 93%
“…Moreover, left fusiform gyrus is located on the surface of temporal and occipital lobes, which is crucial to language function and is modulated by literacy 29 , what is more, it is also the key brain area for bilingual language processing 30 . Additionally, it has also been reported that the fusiform gyrus has a unique visual processing mechanism for text and objects 31 . Practically speaking, the left MOG and left fusiform gyrus were found to be co-related in cognitive, linguistic functions and visual processing 32 .…”
Section: Cortical Thickness Reduction In Visual Center and Visual Promentioning
confidence: 99%
“…mALFF will be accomplished by dividing ALFF value of the whole brain into ALFF value of each voxel. 17 , 40 …”
Section: Methodsmentioning
confidence: 99%